Effects of land-use changes on soil respiration - Gomes, Daniel da Silva; Santos, Teófilo de Medeiros; Barbosa, Alex da Silva; Santos, Sabrina Kelly dos; Melo, Tiago de Sousa; Aquino, Italo de Souza (Journal of Environmental Analysis and Progress, 2022)
In Brazil, soil use and occupation are largely responsible for greenhouse gas emissions, and one of the ways to monitor disturbances to ecosystems is through edaphic respiration, resulting in root respiration and microorganisms’ activity presented in the soil layers. The study aimed to evaluate edaphic respiration in four land-use systems. The research was carried out in four soil use systems: Forest Remnant Area (F); Agroforestry System (AFS); Mandala (M) and Pasture (P), in the Bananeiras-PB countryside. Three soil samples of each system were collected, at 0-20 cm depth, for chemical and physical analysis to characterize them. The carbon dioxide was measured using a methodology described by Grisi and the captures of CO2 were analyzed at night and daytime for eight months. A completely randomized design was used in a 4 x 2 factorial scheme. The lower temperatures, during the night, favored a higher CO2 emission; the pasture system and the AFS showed higher CO2 release in two evaluation shifts; the forest remnant area showed less carbon dioxide release. The pasture area, due to its low vegetation cover, and consequently high temperature and low humidity, presented greater carbon release, in contrast, the remaining forest area, due to its greater vegetation cover, and thus lower temperatures and high humidity, presented less CO2 release.